Oxygen potential, oxygen diffusion, and defect equilibria in UO2±x - Watanabe, Masashi; Kato, Masato (Frontiers in Nuclear Engineering, 2023)
Oxygen potentials and oxygen chemical diffusion coefficient of UO2 were measured by the gas equilibrium method in near stoichiometric region at temperatures of 1673–1873 K. A data set of oxygen potential was made together with literature data and analyzed based on defect chemistry. Oxygen potential of UO2 was determined as function of O/U ratio and temperature, which relational equation to represent was derived. Defect equilibrium constants were evaluated by fitting the experimental data, and defect formation energies were determined to construct a Brouwer diagram, which can represent the relationship of O/U-T-P_(O_2 ). The estimated oxygen Frenkel formation energy found to be 404.5 kJ/mol was in good agreement with literature data. The oxygen chemical diffusion coefficients obtained in this study were generally reasonable values compared with the literature values. The oxygen partial pressure dependence of the oxygen chemical diffusion coefficient was predicted from the evaluated results of the oxygen potential data, but no clear dependence was observed.